Kundenvertretung und Fahrgastrechte im öffentlichen Verkehr. Facetten eines lange vernachlässigten Gebiets der Verkehrsplanung/-politik. - Schiefelbusch, Martin (Deutscher Verkehrs-Verlag, 2004)
Seit gut einem Jahr ist das Stichwort Fahrgastrechte in der Verkehrspolitik in aller Munde. Angeregt durch die Diskussion um das Preissystem der DB AG wird die im Grunde schon lange bestehende, besondere rechtliche Stellung der Bahnfahrgäste zunehmend kritisch gesehen. Vor diesem Hintergrund soll in dem Beitrag die Frage der Fahrgastrechte in den größeren Zusammenhang der Interessenvertretung der Kunden des ÖV gestellt werden. difu

The situation of public transport users has recently been subject of much debate in Germany. In contrast to most other sectors, operators are exempted from civil law obligations requiring producers to compensate consumers for service malfunctions. This situation has come in for much criticism and is now widely seen as incompatible with modern standards of consumer protection. However, a better ex-post settlement of conflicts alone is unlikely to address all aspects of user interests. The paper therefore argues to take a comprehensive look at the various levels of user representation. To do so, a structure of four dimensions is developed: the political, planning, provision and practical level. For each of these, the main issues are discussed and same practical examples of user representation and customer service elements are presented. difu
Keywords: Öffentlicher Verkehr; ÖPNV; Verkehrsplanung; Partizipation; Nutzerbeteiligung; Interessenvertretung; Verkehrsunternehmen; Fahrgast; Kundenorientierung; Fahrgastrecht; Verbraucherschutz